Immunological profiling in type 2 diabetes mellitus and type 2 diabetic kidney disease: insights from single-cell LacNAc sequencing - Xiao, Mengyun; Xu, Zigan; Zhu, Xiaohui; Chen, Jing; Wang, Ru; Wang, Yaxuan; Gao, Xiang; Luan, Shaodong; Pu, Xiaoyan (Frontiers in Endocrinology, 2025)
BackgroundDiabetic kidney disease (DKD), a major complication of type 2 diabetes mellitus (T2DM), is the leading cause of end-stage renal disease (ESRD). Recently, the innate immune system, particularly neutrophils and the process of NET formation, has garnered significant attention for its role in the progression of T2DKD in patients with T2DM. However, the underlying mechanism remains unclear.MethodsWe employed single-cell LacNAc sequencing (scLacNAc-seq) to characterize immune cell populations, glycosylation patterns, and functional alterations in peripheral blood mononuclear cells (PBMCs), focusing on low-density granulocytes (LDGs), from patients with T2DM and T2DKD versus healthy controls (HC). In vitro cultures of primary human neutrophils under high glucose and high glucose plus serum from patients with T2DKD were used to assess NET formation via myeloperoxidase (MPO) detection. Plasma levels of reactive oxygen species (ROS), CXCL8, CXCR2, MPO, and neutrophil elastase (NE) were quantified by ELISA.ResultsPatients with T2DM and T2DKD showed increased LDG counts and glycosylation abundance in FOLR3- and PI3-expressing subclusters. Functional enrichment analysis of overlapping differentially expressed genes (DEGs) and subclusters revealed enrichment in NET formation pathways. In vitro studies promoted NET release, as evidenced by reduced intracellular MPO and elevated supernatant MPO under hyperglycemic conditions. Plasma ROS, CXCL8, CXCR2, MPO, and NE levels were elevated in patients with T2DM and T2DKD than in HCs. Furthermore, enhanced interactions between neutrophils and mononuclear phagocytes (MPs), primarily mediated by the CXCL8/CXCR2 axis, were observed.ConclusionThis study identifies immunological alterations in T2DM and T2DKD, implicating neutrophil-mediated inflammation and NET formation in T2DKD progression. Correlative data suggest that targeting ROS and the CXCL8/CXCR2 pathway may represent potential therapeutic directions, though preclinical validation is warranted.